2019
DOI: 10.3390/met9121269
|View full text |Cite
|
Sign up to set email alerts
|

Study on Surface Longitudinal Crack Formation of Typical Hypoeutectoid Steel Produced on a Caster with Billet and Slab

Abstract: This paper investigates the formation mechanism of typical hypoeutectoid steel with longitudinal cracks produced on a caster with billet and slab. It was found that the microstructure of the proeutectoid ferrite is the most critical factor affecting the longitudinal crack. The formation conditions of the proeutectoid ferrite and the reasonable control direction were determined through experiments and calculations. High-temperature tensile experiments revealed that enhanced cooling did not cause additional crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[4][5][6] Generally, it is suggested that cracks in sulfur-containing steel are initiated by MnS inclusions and ferrite. [7][8][9][10][11][12][13][14] Thus, quality improvements especially the controlment of sulfides in sulfur-containing steels are necessary to ensure the elevated needs of consumer expectations.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Generally, it is suggested that cracks in sulfur-containing steel are initiated by MnS inclusions and ferrite. [7][8][9][10][11][12][13][14] Thus, quality improvements especially the controlment of sulfides in sulfur-containing steels are necessary to ensure the elevated needs of consumer expectations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41,42 ] In addition, it has been reported that proeutectoid ferrite is harmful to the toughness of steel, cracks can be initiated by proeutectoid ferrite. [ 42–45 ] Thus, it is of significant importance to control the precipitation of chain ferrite and thus inhibit the crack propagation during hot‐rolling process.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature control scheme of the thermal expansion experiment ( Figure 7 a) was based on the results of the simulated bloom surface temperature during continuous casting. [ 32,35 ] The sample was maintained at 1100 °C for 10 min to homogenize the temperature and cool to room temperature at three different cooling rates. The linear shrinkage of Steel I during phase transformation is 0.05% greater than that of Steel II, resulting in drastic volume changes of Steel I during phase transformation and easy formation of new cracks or propagation of existing cracks (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Nonetheless, in actual production, a large number of surface cracks are generated in the bloom of sulfur‐containing steel when a specific Mn/S ratio is met. [ 31,32 ] Therefore, the formation mechanism of surface cracks in the bloom of medium carbon sulfur‐containing steel requires further studies.…”
Section: Introductionmentioning
confidence: 99%